(untitled) (Proceedings of International Conference on Special Education, 2015)
In a learning difficulties class of a Special Needs Programme, a teacher’s role is as a teaching staff and an administrator. Teachers are frequently faced with learners’ varied antics and behavioural problems. Amongst the common behavioural problems in any Special Needs Class are aggressive behaviours, passiveness, negative social behaviours and emotional problems. Thus Grand Token (GT) is one technique that has been adopted in managing the varied Special Needs learners’ behavioural problems in this research. The hypothesis is that when Special Needs children are given the trust and responsibility to manage their own behaviours in a form of a contract which they have to adhere to, they will be able to better manage and control their own behaviours. This action research is based on Kemmis and McTaggart Model(1988). 4 Special Needs learners with learning difficulties are the subject of this research. Qualitative data is gathered through a triangulation method which consists of interview sessions with Special Needs Education teacher involved, record of learners attendance and observation of learners ability to complete tasks given in language classes.. Before the learning sessions for the research start, a contract chart which is agreed upon by the learners is first prepared. Based on the qualitative data gained, it has been found that GT is an effective technique to help language teachers deal with learners’ behavioural problems. By using the agreed contract technique, a score of 90% is produced. The results show an increase in school attendance frequency, being active during language classes and an increase in learners’ ability to complete language tasks during lessons.